PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING BERBANTUAN CD INTERAKTIF DAN STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR AKUNTANSI DITINJAU DARI MOTIVASI SISWA SMK DI KABUPATEN BLORA KELAS XI TAHUN PELAJARAN 2013/2014 - Ahmad, Abdurrahman; Joyoatmojo, Soetarno; Murtini, Wiedy (Jurnal Pendidikan Insan Mandiri, 2015)
The purpose of this study are: (1) to determine differences in the effect of the Creative Problem Solving Model-aided learning interactive CD and Student Teams Achievement Division on accounting achievement (2) to determine differences in the effect of high motivation and low motivation on accounting achievement (3) to determine interaction effects of motivation and models of instruction on learning and accounting achievement. The population were students of vocational high school in Blora. Sampling by cluster random sampling technique. The study sample consisted of 95 students.Based on the analysis of data, it can be concluded that: (1) there are differences in the effect of the learning model of CPS assisted interactive CD and STAD on achievement of accounting (cognitive achievement of Fo at 9.932 > Ft 2.70), (affective achievement Fo amounted to 5.839 > Ft 2.70), (psychomotor achievement of Fo at 5.095 > Ft 2.70) (2) there are differences in the effect of high motivation and low motivation on achievement of accounting (cognitive achievement of Fo at 4.126 > Ft 2.70), (results affective learning Fo of 5.689 > Ft 2.70), (psychomotor achievement of Fo by 5.723 > Ft 2.70) (3) there was an interaction effect of models of learning and motivation on achievement of accounting (cognitive achievement of Fo at 4.136 > Ft 2.70), (affective achievement of Fo at 4.341 > Ft 2.70), (psychomotor achievement of Fo at 4.570 > Ft 2.70). Keywords: creative problem solving aided interactive CD, learning motivation and learning achievement